Professionalism, ethics and good medical practice: from lofty ideals to bedside medicine - A.S. Dissanayake; I.H. Rajapakse; D.J.D. Mihiran (Sri Lanka College of Internal Medicine, 2022)
"The difficulty with teaching medical professionalism is that there seems to be no agreement on what the term exactly means" Catherine D DeAngelis, Editor in Chief Emerita, JAMA